2020
DOI: 10.3390/su12041656
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Inter-Relationships between Urban Decline and Urban Sprawl in City-Regions of South Korea

Abstract: This paper identifies inter-relationships between the urban decline in core areas and urban sprawl in hinterlands using 50 city-regions of South Korea. We measured decline- and sprawl-related indicators and estimated a simultaneous equations model using Three-Stage Least Squares. The results show that population decline and employment decline have a different relationship with urban sprawl. While population decline has a negative impact on the urban sprawl in the density aspect, employment decline worsens the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This is certainly very contradicts to the economic theory of development explained by Rostow in Hunter (2012), which stated that ease of accessibility through transportation could improve the quality of life and welfare of the community. This condition is also supported by research on the influence of urban sprawl in South Korea, which showed that economic factors such as employment could affect the formation of the process of urban expansion from the city center to the periphery, especially in morphological aspects (Hwang and Woo, 2020).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is certainly very contradicts to the economic theory of development explained by Rostow in Hunter (2012), which stated that ease of accessibility through transportation could improve the quality of life and welfare of the community. This condition is also supported by research on the influence of urban sprawl in South Korea, which showed that economic factors such as employment could affect the formation of the process of urban expansion from the city center to the periphery, especially in morphological aspects (Hwang and Woo, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…Based on the study of urban sprawl in the outskirts of South Korea (Hwang and Woo, 2020), stated that one of the factors that encourage urban spreading is the spread of population from the city center to the suburbs. This also occurs in the 1000 meter radius area of corridor 1 of BRT Trans Semarang, which covers 50 villages from 8 sub-districts, where the results of data processing in this study indicate that it occurs there is a change in the direction of the outskirts of the city, the majority of which head toward the Penggaron marked with a solid color (relatively large population) on the map.…”
Section: Resultsmentioning
confidence: 99%
“…South Korean metropolises, including Seoul, are considered less affected by sprawl due to green belt policies and their mountainous geography (S. Lee, 2018). Yet smaller cities have exhibited a tendency for urban sprawl that showed a positive correlation with urban decline (Hwang, 2017). In small to medium South Korean cities that may experience further population decrease due to a low birth rate, DIY housing constructions in the hinterland may accelerate the urban decline.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this logic, another way of expressing the fact that the relation between rank and size is linear is that the distribution of city sizes adheres to the power law [43]. As a typical form of the Zipf law, Equation (1) indicates the population of the city ranked r:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Why do cities grow and decline? China faces this question, as its urban growth is steadily decreasing, and so does Korea, which has entered a phase of full-scale urban decline [1][2][3]. It is also an important issue in Western Europe and Japan, where urban decline has been progressing for a prolong time.…”
Section: Introductionmentioning
confidence: 99%